The fabrication of lead titanate ceramics by a two-stage sintering technique - R. Wongmaneerung (2018)
In this work, a two-stage sintering technique, which began with an initial heating at lower temperature and followed by higher temperature sintering, was employed in the production of PbTiO3ceramics. Effects of designed sintering conditions on phase formation, densification, microstructure and dielectric properties of the ceramics were characterized via X-ray diffraction (XRD), Archimedes method, scanning electron microscopy (SEM) and dielectric measurement, respectively. The potentiality of a two-stage sintering technique as a low-cost and simple ceramic fabrication to obtain highly dense and pure lead titanate ceramics was demonstrated. It has been found that, under suitable conditions, the perovskite phase of densified PT ceramics with reasonable dielectric properties may be achieved with equivalent to those obtained from a single-stage sintering technique. © 2007 Springer Science+Business Media, LLC.